2022
DOI: 10.3390/su14095151
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Some Wild Olive Phenotypes (Oleaster) Selected from the Western Mountains of Syria

Abstract: This study presents the evaluation of some technological and production specifications of 20 selected wild olive (oleaster) phenotypes from Hama Province, western–central Syria. The analyses of oil quantity showed that the olive oil (OO) extracted ranged from 10.43 to 29.3%. The fatty acid composition determined by gas chromatography (m/m%, methyl esters), conforming to commercial standards, showed the percentages of palmitic (ranged 13.2–15.06%), stearic (2.27–4.2%), arachidic (0.42–0.7%), palmitoleic (0.73–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…Considering the quantities and the different phenol fractions found, it can be stated that some Maltese genotypes have important radical scavenging, antioxidant and anti-inflammatory properties [ 42 , 43 , 44 , 45 , 46 ]. The main phenolic compounds in the samples under investigation were secoiridoids and their derivatives, as has already been found in other studies [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The contribution of phenolic alcohols, such as hydroxytyrosol and tyrosol, of flavonoids with rutin and luteolin 7-glycoside and of acid phenols (particularly vanillic acid) was relevant.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Considering the quantities and the different phenol fractions found, it can be stated that some Maltese genotypes have important radical scavenging, antioxidant and anti-inflammatory properties [ 42 , 43 , 44 , 45 , 46 ]. The main phenolic compounds in the samples under investigation were secoiridoids and their derivatives, as has already been found in other studies [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The contribution of phenolic alcohols, such as hydroxytyrosol and tyrosol, of flavonoids with rutin and luteolin 7-glycoside and of acid phenols (particularly vanillic acid) was relevant.…”
Section: Discussionsupporting
confidence: 76%
“…The correlation between small fruit, low oil content and thin flesh in wild olive genotypes is well established. In fact, olives produced from wild olives usually have an oil content between 5 and 10% [ 37 , 38 , 39 ]. In this study, some genotypes, such as 2Mtarfa and 1Pembroke (both E2), showed very low oil values, at just over 2% of their fresh fruit weights, also as a consequence of the prevalence of the stone with respect to the pulp.…”
Section: Discussionmentioning
confidence: 99%